Answer:
(3,3)
Step-by-step explanation:
Hope this helps
Answer:
f(3) = 3
Step-by-step explanation:
f(1) = 1
f(2) = 2
f(n) = f(n − 2) + f(n − 1)
f(3) = f(3 - 2) + f(3 - 1)
= f(1) + f(2) = 1 + 2 = 3
Special Note: Have you heard of the Fibonacci sequence?
The formula f(n) = f(n − 2) + f(n − 1) is used to find the terms of the of the Fibonacci sequence
Answer:
add 26 to 7 and there is your anwser
Answer is 3.
3,6
3,6,9,12,15,18,21,24,27
3,6,9,12,15,18,21,24,27,30
Answer:
it would be the first one 16